PESANTREN SALAF: PERUBAHAN SOSIAL DAN SUBLIMASI IDENTITAS DENGAN KOMBINASI TASAWUF, FIQIH DAN TAUHID (Model Pesantren di Kabupaten Tasikmalaya Jawa Barat) - Muhammad Solahudin; Ecep Ismail; Irwan Abdurrohman (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
On the one hand, in the environment of the Pesantren salaf community, a kind of environment and tradition is formed which shows its unique, even unique characteristics, which are only understood by the community. Gus Dur, in this case, stated that the Pesantren salaf community is a community that has its own subcultural in the middle of society with the complexity of the problems in it. But on the other hand, there is a very rapid development of science and technology, so it demands pesantren salaf to make changes to adjust to the times, both in terms of the education system, the boarding school environment, institutions, leadership patterns, and others. Therefore, the study contained in the title